If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(1 + 3b) = 2 (1 * 10 + 3b * 10) = 2 (10 + 30b) = 2 Solving 10 + 30b = 2 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 30b = 2 + -10 Combine like terms: 10 + -10 = 0 0 + 30b = 2 + -10 30b = 2 + -10 Combine like terms: 2 + -10 = -8 30b = -8 Divide each side by '30'. b = -0.2666666667 Simplifying b = -0.2666666667
| y-2(-1)=3 | | 4(x-3)-6=18 | | H+12=14 | | 2y-4(-2)=8 | | Y-9=15 | | 2y-4(-1)=8 | | 19=-29+5 | | -14+C=-12 | | 6x+8-3x=2(x-2) | | -4(8-7x)=80 | | 2y-4(1)=8 | | 3x-(2x-5)=8 | | 43+(x-5)+(2x-15)=180 | | -2+N=-2 | | 2y-4(2)=-8 | | 0.3x-7=1/2 | | M+(-2)=6 | | -4+B=12 | | -7+(-34)+(-13)+(-16)= | | R-6=12 | | 4.3+B=5.8 | | 7(x-4)=6x+8 | | 7k-5=-5 | | K+5=6 | | -7(-6x-7)=175 | | (x*18)+(x*20)-x^2=280 | | 3.8=T-4.6 | | x/4=-9 | | 25+(-4)+(-6)+(-25)= | | 4(5x+7)=148 | | A+6=-9 | | -3(x+5)-2(-x-4)=17.5 |